1999
DOI: 10.1177/001789699905800310
|View full text |Cite
|
Sign up to set email alerts
|

Identifying primary research on electronic databases to inform decision-making in health promotion: the case of sexual health promotion

Abstract: Evidence of the effectiveness of health promotion to support decision-making has become increasingly important to health promotion practitioners and policy-makers. Primary research on effectiveness, however, is not always easily accessible. This study aimed to contribute to strategies for facilitating access to this research by exploring the development and implementation of search strategies for identifying effectiveness research, in the area of sexual health promotion, on five commonly used electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…PubMed), a wide range of smaller databases needs to be searched in order to identify research for reviews that aim to maximise external validity [ 8 ]. In practice, this means adopting a multi-layered approach to searching which combines: extensive Boolean searches of electronic bibliographic databases, specialised registers and websites; with individual approaches to authors and key informants; and the following of ‘citation trails’ (identifying which papers are cited by a relevant study and which papers in turn cite the paper that it is reported in) [ 9 ]. Of these three approaches, searching databases yields around three quarters of the studies finally included [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PubMed), a wide range of smaller databases needs to be searched in order to identify research for reviews that aim to maximise external validity [ 8 ]. In practice, this means adopting a multi-layered approach to searching which combines: extensive Boolean searches of electronic bibliographic databases, specialised registers and websites; with individual approaches to authors and key informants; and the following of ‘citation trails’ (identifying which papers are cited by a relevant study and which papers in turn cite the paper that it is reported in) [ 9 ]. Of these three approaches, searching databases yields around three quarters of the studies finally included [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Query limits applied to enhance the specificity of this initial search included the terms professional values, code of ethics, patient care, care delivery systems, management approach, decision making, professional relationships, interdisciplinary relationships, salary and compensation [ 24 ]. The high specificity of the augmented search did not correspond to a high sensitivity, which meant numerous articles captured using the initial search terms were excluded [ 24 ]. The tradeoff was to proceed with the initial time-consuming search strategy that ensured all relevant articles meeting specified criteria were included.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously, we found that enhancing the search with additional terms compromised sensitivity, which meant numerous relevant articles would have been left out. This paradox can be explained by an imprecise alignment between the key words describing our concepts of interest and vocabulary contained in the databases we searched [ 24 ]. For example, the term closest in resemblance to the conceptual meaning of patient care delivery systems in PubMed was professional delegation , which when combined with nursing and low-income countries did not yield any results.…”
Section: Discussionmentioning
confidence: 99%
“…Harden et al [36] reported data on the time needed for developing, testing, and implementing a search strategy for MEDLINE for the topic ''sexual health promotion'' (45 hours). However, the approach selected was similar to our own.…”
Section: Discussionmentioning
confidence: 99%